Taxation of social media advertisements - ORTAÇ, F. Rifat; AKÇAY, Deniz (My University, 2016)
Today, the use of Internet and in particular social media as advertising tools brings the question of how the advertisement in social media should be taxed. This is not only seen as a problem in our country, but in the international platform as well. In the first part of the study, the definition of social media is given; in the second part, Social Media Brand Communities and Fun Pages are discussed; in the third part, a comparison of Social Media Con- tents and Public Goods, Global Public Goods and Club Goods is made; in the fourth part that Conclusion and Suggestions how social media is taxed is discussed.
Keywords: Social Media; Taxation of Social Media; Brand Communities; Internet Advertisement